GENETIC DIVERSITY IN BAMBARA GROUNDNUT (Vigna subterranean) AS REVEALED BY MOLECULAR WEIGHTS OF THE SEEDS’ PROTEINS (Bangladesh Journal of Plant Breeding and Genetics, 2018)
Nine accessions of Bambara groundnut (Vigna subterranea (L.) Verdc.,syn. Voandzeia subterranea (L.) Thouars ex DC.)  obtained from National Centre for Genetic Resources and Biotechnology (NACGRAB), Ibadan, Oyo state, were assessed for their genetic and phylogenetic relatedness through electrophoretic analysis of the seed proteins. 0.2g of the seeds were weighed and macerated with mortar and pestle in 0.2M phosphate buffer containing 0.133M of acid (NaH2PO4) and 0.067 of base (Na2HPO4) at pH 6.5. Protein characterization with standard marker revealed that the seeds of the nine accessions contained proteins (B.S.A, Oval Albumin, Pepsinogen, Trypsinogen and Lysozyme) with molecular weights ranging from 66kda and above, 45 – 65 kDa, 44 – 33 kda, 32-24 kDa and 23-14 kDa, respectively. The student T-test revealed that accessions B, C, E, F, H and I have molecular weights not significantly different from one another (P0.05). All the accessions had at least two proteins and two major bands in common. The study revealed intra-specific similarities and genetic diversity in protein contents among the nine accessions of Bambara groundnut (Vigna subterraranea (L.) Verdc.syn